1994
DOI: 10.1007/bf00374674
|View full text |Cite
|
Sign up to set email alerts
|

Hexose transport across the apical and basolateral membrane of enterocytes from different regions of the chicken intestine

Abstract: The properties of hexose transport across the apical and basolateral membranes of chicken enterocytes have been studied in the small and large intestine. Results show that (a) isolated epithelial cells from all segments except the coprodeum can accumulate 3-O-methylglucose (Glc3Me) against a concentration gradient, by a Na(+)-dependent and phloridizin-sensitive mechanism. (b) The cell cumulative capacity for Glc3Me (control/phloridizin-incubated cells) is lower in the small intestine than in the large intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…From a regional point of view, the small intestine showed a considerable homogeneity in MAF at the day of hatch but in 6-wk-old chickens the duodenum and jejunum increased their surface area whereas the ileum remained unchanged. Isolated enterocytes from proximal segments (duodenum, jejunum) of 4-to 7-wk-old chickens, were shown to be better suited for apical hexose uptake than the ileum (Ferrer et al, 1994). Both observations suggested a morphological and functional correlation, which had to be considered to understand the physiology of the digestive system.…”
Section: Surface Area and Nutrient Absorption During Developmentmentioning
confidence: 96%
“…From a regional point of view, the small intestine showed a considerable homogeneity in MAF at the day of hatch but in 6-wk-old chickens the duodenum and jejunum increased their surface area whereas the ileum remained unchanged. Isolated enterocytes from proximal segments (duodenum, jejunum) of 4-to 7-wk-old chickens, were shown to be better suited for apical hexose uptake than the ileum (Ferrer et al, 1994). Both observations suggested a morphological and functional correlation, which had to be considered to understand the physiology of the digestive system.…”
Section: Surface Area and Nutrient Absorption During Developmentmentioning
confidence: 96%
“…The Na + ‐coupled glucose uptake across SGLT1 is present in all regions of the small and large intestine of chicken and the capacity to transport glucose decreased from the proximal to distal regions of the small intestine (Obst and Diamond, 1989; Ferrer et al., 1994). In our previous study (Awad et al., 2005a), it has been shown that DON inhibited Na + ‐ d ‐glucose co‐transport in the proximal jejunum of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…All regions of the lower intestine also contribute to the resorption of ureteral electrolyte and fluid (Skadhauge, 1993). Furthermore, the proximal caecum and the rectum can also absorb Na¤ cotransported with glucose and amino acids (Lind et al 1980;Moret o & Planas, 1989;Ferrer et al 1994b;Amat et al 1999). All these functions are affected by the NaCl status of the animal since restriction of Na¤ intake results in adaptive regulation, especially in the lower intestine, where there is a marked increase in the apical epithelial Na¤ channel (ENaC; Goldstein et al 1997) and the Na¤-H¤ exchanger (NHE2; Donowitz et al 1998) activities, and in the short-circuit current (Thomas & Skadhauge, 1982;Amat et al 1988).…”
mentioning
confidence: 99%